2019
DOI: 10.1002/ams2.471
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of appropriate indications for the use of sivelestat sodium in acute respiratory distress syndrome: a retrospective cohort study

Abstract: Sivelestat sodium, a selective neutrophil elastase inhibitor, is the only commercially available, specific therapy for acute respiratory distress syndrome (ARDS); however, its clinical efficacy is controversial. We aimed to evaluate appropriate indications for its use in ARDS. Methods: We studied 66 patients with ARDS who were treated with sivelestat sodium. They were divided into survivors (n = 37) or non-survivors (n = 29) at 60 days, and clinical characteristics were analyzed. Results: Patients' backgrounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…Specifically, NE facilitates the invasion of SARS-CoV-2 into host cells and can also damage lung tissues directly. The role of NE in patients with ARDS, including COVID-19, and sepsis have been reported in different studies [104][105][106][107]. Moreover, in an experimental mice model, Ogura et al reported that NE deficiency improves myocardial injury in post-myocardial infarction [108].…”
Section: Neutrophil Elastase Inhibitorsmentioning
confidence: 99%
“…Specifically, NE facilitates the invasion of SARS-CoV-2 into host cells and can also damage lung tissues directly. The role of NE in patients with ARDS, including COVID-19, and sepsis have been reported in different studies [104][105][106][107]. Moreover, in an experimental mice model, Ogura et al reported that NE deficiency improves myocardial injury in post-myocardial infarction [108].…”
Section: Neutrophil Elastase Inhibitorsmentioning
confidence: 99%
“…In a meta-analysis study, sivelestat failed to improve the survival of patients with ARDS ( Tagami et al, 2014 ). However, a retrospective cohort study with 66 ARDS patients demonstrated that sivelestat treatment yields positive outcomes ( Maki et al, 2020 ). In particular, aerosol- or nebulizer-dosed NE inhibitors significantly improved their efficacy and lowered adverse effects ( Barth et al, 2020 ).…”
Section: Drugs Targeting Neutrophils For Covid-19 Associated Ardsmentioning
confidence: 99%
“… 226 Sivelestat, a potent NE inhibitor approved in Korea and Japan, can ameliorate acute lung injury. 227 A retrospective cohort study showed that sivelestat exhibited positive outcomes in patients with ARDS, 228 indicating that NE inhibitor might be beneficial for patients with COVID-19. In addition, A randomized, placebo-controlled phase Ib/II clinical trial of Alvelestat treatment for COVID-19 with ARDS has been completed with no results published (NCT04539795).…”
Section: Netosis and Sars-cov-2mentioning
confidence: 99%